STRATEGI PEMBELAJARAN MEMBACA AL-QUR’AN BERBASIS BAHASA ISYARAT DI SMPLB ( STUDI KASUS PADA SISWA DI SLB NEGERI PKK PROVINSI LAMPUNG) : (Case Study on Students at the PKK State Special Needs School in Lampung Province) - Liatul Karisma; Meriyati Meriyati; Muhammad Mustofa (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
This study was motivated by the importance of teaching deaf students to read the Qur’an, as their hearing impairments necessitate learning strategies tailored to their visual learning styles. Teaching deaf students to read the Qur’an cannot be done solely through auditory methods; therefore, the use of sign language as a communication medium is essential in the learning process. This study aims to analyze sign language-based Quran reading learning strategies and to identify the advantages and challenges in their implementation among deaf students at the SMPLB Negeri PKK in Lampung Province. This study employs a qualitative approach using the case study method. Data collection techniques include observation, interviews, and documentation. Data analysis utilized the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the learning strategies were implemented through the use of sign language, visual aids, hand gestures, the introduction of sign language Hijaiyah letters, and the gradual teaching of vowel marks. These strategies helped students understand the Qur’an reading material more easily. The advantages include making learning more communicative, visual, and interactive, while the challenges lie in communication limitations and the need for intensive repetition of the material.